(untitled) (New Collegium, 2020)
University-School clusters: Best practices and the prospects for their adaptation to Ukrainian context : the XVIII International Scientific and Practical Conference (14-th Febuary 2020, Kharkiv Univ. of Humanities “People’s Ukrainian Acad”. Modern educational processes are changing all the elements of the university world. In this case we deal with the fundamentally different university management models under the condition of their integration into cluster systems. Special attention is paid to the needs for changing decision-making models. All this leads to a great increase and differentiation of the requirements for the rectors’ body as an important subject of the university life. Under the condition of the educational process clustering the modern rector is supposed to manage processes, learn new management approaches and acquire new competences at the same time. The task is quite complicated and requires both analysis and working out certain new approaches to the formation and development of the rectors’ body.